Visitation in urban natural areas: a study on the attractiveness of the Parque Estadual do Cocó (Fortaleza, Ceará, Brazil) - Lindoso, Tais; de Paula, Davis (Geografares, 2023)
Due to the growing demand for green spaces with conditions for the development of leisure activities, protected areas such as parks are very popular. The Parque Estadual do Cocó (PEC, in Portuguese), located in the city of Fortaleza, is a case in point. Therefore, the aim of this study is to identify the visitor profiles and the radius of attraction of the PEC. For this purpose, 233 structured forms were filled in by the visitors who were present. The forms were statistically analyzed using Excel. Google Maps was used to calculate the displacement of visitors, considering the displacement routes. This resulted in a minimum distance of 0.75 km and a maximum of 23.2 km, with 68 neighborhoods as points of origin for the visitors. The radius of influence of the PEC was found to be 12.14 km, showing its importance as a recreational area.